2019
DOI: 10.1016/j.scispo.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on dry-land strength and conditioning training on swimming performance

Abstract: Objectives.-The objective of this review was to examine the effects of dry-land strength and conditioning (S&C) training on swimming, and starts and turns performances. News.-S&C training is a common practice in swimming aiming to enhance performance or to prevent injuries. However, studies regarding the effects of S&C on swimming performance are scarce; the influence of age, gender or competitive level is even scarcer. Prospects and projects.-After a structured literature search, sixteen studies were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
(149 reference statements)
0
19
0
1
Order By: Relevance
“…Resistance exercise training can be functionally defined as the progressive overload of a skeletal muscle that is characterized by high muscle contraction force and anaerobic ATP resynthesis (Schumann & Rønnestad, 2019). Past studies involving a dryland resistance strength training intervention added to swimming training load have reported significant improvements in performance (N M Amaro et al, 2019;Crowley, Harrison, & Lyons, 2017;Schumann & Rønnestad, 2019). Girold et al (2012), Girold et al (2007), Strass (1988) and Aspenes et al (2009) all found that traditional upper-limb resistance-training methods increased dryland strength and consequently improved swimming performance (Aspenes, Kjendlie, Hoff, & Helgerud, 2009;Sébastien Girold et al, 2012;Sebastien Girold, Maurin, Dugue, Chatard, & Millet, 2007;Strass, 1988)Each of these studies employed training plans with low repetition ranges (1-6 repetitions), a low number of sets (≤3 sets), and high velocity increase.…”
Section: Strength Training In Swimmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance exercise training can be functionally defined as the progressive overload of a skeletal muscle that is characterized by high muscle contraction force and anaerobic ATP resynthesis (Schumann & Rønnestad, 2019). Past studies involving a dryland resistance strength training intervention added to swimming training load have reported significant improvements in performance (N M Amaro et al, 2019;Crowley, Harrison, & Lyons, 2017;Schumann & Rønnestad, 2019). Girold et al (2012), Girold et al (2007), Strass (1988) and Aspenes et al (2009) all found that traditional upper-limb resistance-training methods increased dryland strength and consequently improved swimming performance (Aspenes, Kjendlie, Hoff, & Helgerud, 2009;Sébastien Girold et al, 2012;Sebastien Girold, Maurin, Dugue, Chatard, & Millet, 2007;Strass, 1988)Each of these studies employed training plans with low repetition ranges (1-6 repetitions), a low number of sets (≤3 sets), and high velocity increase.…”
Section: Strength Training In Swimmingmentioning
confidence: 99%
“…important for sprint swimming performance(N M Amaro et al, 2019;Nuno M Amaro, Marinho, Marques, Batalha, & Morouço, 2017;Manning, Dooly-Manning, Terrell, & Salas, 1986;Sadowski, Mastalerz, Gromisz, & Niźnikowski, 2012). A recent systematic review found training for power positively influences short-distance swimming(N M Amaro et al, 2019). A training program based on power was applied to a group of adolescent swimmers (16.49 ± 0.84 years)(Sadowski et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is recognised that strength training improves swimming performance. 1 In a short-distance swimming race (i.e. 50-200m), the strength of the lower extremities takes greater preponderance than in a long-distance endurance challenge (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recently, a review indicated that some strength training could be questionable in low-level competitive swimmers. 1 The aim of this study was to observe changes in the thigh girth, hamstring flexibility, squat jump height, and 200m swimming time trial in recreationally-trained adult swimmers after PT.…”
Section: Introductionmentioning
confidence: 99%